Endometrial pathology in abnormal uterine bleeding - Rajagopal, Indu; Thomas, Beena Mary; Rao, Vidyadhar N.K. Rama (International Journal of Research in Medical Sciences, 2019)
Background: Abnormal uterine bleeding (AUB) is a common presenting symptom in gynecological outpatient department. Endometrial sampling could be used as the first diagnostic step in AUB. Aim of our study was to evaluate the endometrial causes of AUB and to observe the incidence of various pathology in different age groups. Methods: A study was conducted on 167 patients who presented with AUB, during the period from July 2015- January 2017.All endometrial curettage and hysterectomy specimens received in the Department of Pathology, Kannur Medical College during this period were included. Results: Maximum numbers of patients were in the perimenopausal age group and normal cycling endometrium was the commonest pattern observed (41.3%).Abnormal patterns noted were hyperplasia without atypia (20.9%), disordered proliferative pattern (16.1%) and endometrial carcinoma (1.7%). Conclusion: Histopathological examination of endometrium showed wide spectrum of lesions from normal endometrium to malignancy. Accurate analysis of endometrial sampling is important in the management of AUB.